Palliative care made visible: Developing a rural model for the Western Cape Province, South Africa - Victoria O'Brien; Louis S. Jenkins; Margie Munnings; Hilary Grey; Zilla North; Helise Schumann; Elmari De Klerk-Green (AOSIS, 2019)
Introduction: Caring for people with life-threatening illnesses is a key part of working in health care. While South Africa launched the National Policy Framework and Strategy for Palliative Care 2017-2022, integrating palliative care into existing public health care is in its infancy. Most patients in the Western Cape have poor access to palliative care, an inequality felt hardest by those living in rural areas. Building the model: In 2018, with district wide institutional managerial support, a palliative care model for rural areas was initiated in the Western Cape. The process involved setting up hospital- and community-based multi-professional palliative care teams, initiating weekly palliative care ward rounds, training champions in palliative care and raising awareness of palliative care and its principles. Discussion: Establishing regular ward rounds has changed the way patients needing palliative care are managed, particularly in challenging the mindsets of specialist departments. The emergence of the multi-professional team listening and planning together at the patient's bedside has restored some of the dignity and ethos of patient-centred care, which is a core principle of the provincial Health Care 2030 vision. Conclusion: In a short time period, we have managed to build a service that aims to improve care for palliative patients in rural areas. Its strength lies in a multi-professional patient-centred approach and improved communication between different components of the health system, providing a more seamless service that supports patients when they need it most.